2013
DOI: 10.1080/07391102.2013.825757
|View full text |Cite
|
Sign up to set email alerts
|

The design of a peptide sequence to inhibit HIV replication: a search algorithm combining Monte Carlo and self-consistent mean field techniques

Abstract: We developed a search algorithm combining Monte Carlo (MC) and self-consistent mean field techniques to evolve a peptide sequence that has good binding capability to the anticodon stem and loop (ASL) of human lysine tRNA species, tRNA(Lys3), with the ultimate purpose of breaking the replication cycle of human immunodeficiency virus-1. The starting point is the 15-amino-acid sequence, RVTHHAFLGAHRTVG, found experimentally by Agris and co-workers to bind selectively to hypermodified tRNA(Lys3). The peptide backb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…Examination of the energies (Table ) shows that the five complexes exhibit little change in the GBSUR energy, a medium‐size change in the intermolecular VDW energy and TS energy, and a large change in the intermolecular ELE + EGB energy. In our prior work on recognition mechanisms between peptide and RNA, we have found that the intermolecular ELE + EGB energy is responsible for the binding affinity and the intermolecular VDW energy is responsible for the binding specificity. Our simulation reveals that adding a peptide stability term with a weighting of λ = 0.010 to the score function greatly enhances the binding affinity between peptide and ASL Lys3 due to the notable decrease in the ELE + EGB energy.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Examination of the energies (Table ) shows that the five complexes exhibit little change in the GBSUR energy, a medium‐size change in the intermolecular VDW energy and TS energy, and a large change in the intermolecular ELE + EGB energy. In our prior work on recognition mechanisms between peptide and RNA, we have found that the intermolecular ELE + EGB energy is responsible for the binding affinity and the intermolecular VDW energy is responsible for the binding specificity. Our simulation reveals that adding a peptide stability term with a weighting of λ = 0.010 to the score function greatly enhances the binding affinity between peptide and ASL Lys3 due to the notable decrease in the ELE + EGB energy.…”
Section: Resultsmentioning
confidence: 98%
“…In previous papers, we developed a hybrid search algorithm combining Monte Carlo (MC), Self‐consistent mean field theory (SCMF) and the concerted rotation move (CONROT) techniques to evolve peptide sequences that recognize and bind to ASL Lys3 . The advantage of our hybrid search algorithm is that it allows us to iterate between sequence mutations and conformation changes, thereby optimizing the peptides simultaneously in sequence space and in conformation space during the evolution process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conformation of boxB RNA and the backbone conformation of the peptide are fixed during sequence evolutions. Unlike our previous algorithm [21], the new algorithm does not need the self-consistent mean field technique to determine appropriate rotamer combinations from a library of fixed sidechain configurations. Instead we add an energy minimization step to determine optimal sidechain configuration for the amino acid repacking.…”
Section: Structures and Methodsmentioning
confidence: 99%
“…DPP-Fe cofactor. In our previous work [21], a search algorithm combining MC and SCMF techniques was developed to evolve peptide sequences that have good binding capability to the anticodon stem and loop (ASL) of human lysine tRNA species, viz . ASL Lys3 , with the ultimate purpose of breaking the replication cycle of human immunodeficiency virus-1.…”
Section: Introductionmentioning
confidence: 99%